Advancement of Tooling for Spark Plasma Sintering. Issue 11 (4th March 2015) - Giuntini, Diletta; Raethel, Jan; Herrmann, Mathias; Michaelis, Alexander; Olevsky, Eugene A.
Abstract : A combined experimental and numerical study is conducted to investigate temperature nonhomogeneities within a Spark Plasma Sintering tooling setup. Radial thermal gradients through a powder compact are encountered, a cause of microstructural nonuniformities in sintered specimens, which tend to become more significant when increasing the setup's characteristic size. In the insulating silicon nitride powder compact employed for the experimental procedures, a double pyrometer arrangement detects a strong temperature disparity between the overheated die and the area adjacent to the tooling's axis. A previous finite‐element simulations campaign had individuated a possible solution in a novel punch design, consisting in the drilling of three concentric ring‐shaped holes according to a specific geometrical pattern, whose efficacy is here experimentally verified. Further punch optimization strategies are drawn, involving a refinement of the three‐rings geometry by linearly varying the drilled holes characteristic dimensions along the radial direction, or the selective coating and consequent insulation of the punch cross section with a thin layer of hexagonal boron nitride. Ideal configurations are identified, consisting in a concentration of the graphite punch's mass at its center by means of a tailored holes pattern, or in the coating of a portion of the conventionally shaped punch with boron nitride.